Family Support in the Tradition of Mappanetta' Isi as an Effort to Maintain Dental Health in the Bugis Community in South Sulawesi - Asrina, Andi; Reski, Muhammad Alif; Abbas, Hasriwiani Habo; Yusriani, Yusriani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Dental and oral health is very important because it is one of the highest indicators of individual health and disease that people complain about so various ways are done by individuals to maintain dental health both medically and traditionally. Various traditions of caring for teeth have been carried out for generations by the community, one of which is Mappanetta' isi which is a traditional way of the Bugis community in South Sulawesi in maintaining dental health. Objective: To analyze family support in the Mappanetta' isi tradition as an effort to maintain dental health in the Bugis community in South Sulawesi. Method: research is descriptive qualitative with an ethnographic approach using observation techniques, in-depth interviews and documentation during the research. Informants consisted of 1 community leader as a key informant, 1 health officer and family as support and 4 main informants of purposively selected research with the criteria of the Bugis community who preserve the tradition of mappanetta' isi. The data that has been collected will be reduced, categorized, and presented in narrative form. Data analysis with taxonomy, and data validity plan using triangulation. Results: It was found that the preservation of the mappanetta' isi tradition could not be separated from family support or other social support. The role of the family is always to introduce and carry out the tradition to its generation using simple tools, this strengthens the instillation of values and beliefs of the Bugis community in Wajo Regency on mappanetta' isi dental care. Conclusion: Family support is a factor in the preservation of the mappanetta' isi tradition, so that the custom can be accepted and is still practiced today.